Upstairs, downstairs. Season 2 [videorecording (DVD)] - Thomas, Heidi, 1967-; Hawes, Keeley, 1976-; Stoppard, Ed; Scarborough, Adrian (Distributed by Warner Home Video, 2012)
Now a well established household in the heart of London, life in Eaton Place has moved on; Lady Agnes and Sir Hallam's family is complete with the addition of two small children and London has settled into an uneasy peace with the apparent aversion of war. Yet below the surface of a well-run household, both upstairs and downstairs are harboring life-changing secrets. As romance, heartbreak and revelation engulf the household; its inhabitants discover that the real threat is closer to home.